2007
DOI: 10.1021/np070095j
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrosides and Tocopherol Trimers from the Seeds of Euryale ferox

Abstract: Two new cerebrosides, ferocerebrosides A (1) [(2S,3R,4E,8E,2'R)-1-O-(beta-glucopyranosyl)-N-(2'-hydroxydocosanoyl)-4,8-sphingadienine] and B (2) [(2S,3R,4E,8E,2'R)-1-O-(beta-glucopyranosyl)-N-(2'-hydroxytetracosanoyl)-4,8-sphingadienine], two new tocopherol trimers, ferotocotrimers C (5) and D (6), and two known tocopherol trimers, IVb (3) and IVa (4), were isolated from the seeds of Euryale ferox. Their structures were determined on the basis of spectroscopic data, especially 1D and 2D NMR experiments. Compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 21 publications
0
23
0
1
Order By: Relevance
“…In traditional oriental medicine, E. ferox seeds have been used to treat chronic diarrhea, leukorrhea, polydipsia, renal disease, ischemic heart disease, and mouth dryness [ 2 , 3 , 4 ]. Previous studies indicated that E. ferox seeds contained tannins, tocopherol polymers, fucosterol, resorcinol, pyrogallol, cyclic dipeptides, glucosylsterols, cerebrosides, and polyphenols [ 5 , 6 , 7 , 8 ]. E. ferox seed extracts have shown significant antioxidant activity, effects on cell-mediated immunity, neuroprotective effects, and cardioprotective properties, including the prevention of myocardial ischemic reperfusion injury [ 3 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In traditional oriental medicine, E. ferox seeds have been used to treat chronic diarrhea, leukorrhea, polydipsia, renal disease, ischemic heart disease, and mouth dryness [ 2 , 3 , 4 ]. Previous studies indicated that E. ferox seeds contained tannins, tocopherol polymers, fucosterol, resorcinol, pyrogallol, cyclic dipeptides, glucosylsterols, cerebrosides, and polyphenols [ 5 , 6 , 7 , 8 ]. E. ferox seed extracts have shown significant antioxidant activity, effects on cell-mediated immunity, neuroprotective effects, and cardioprotective properties, including the prevention of myocardial ischemic reperfusion injury [ 3 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These sphingadienes (SDs) are cytotoxic to insect cells and are structurally similar to SDs that comprise the sphingoid base backbone of soy sphingolipids. Complex sphingolipids containing SDs and sphingatrienes are found in aquatic plants used for medicinal purposes in traditional oriental medicine (15-17). Thus, we hypothesized that SDs might be the active component of soy that inhibits intestinal tumors.…”
Section: Introductionmentioning
confidence: 99%
“…abiesatrine J or 3,4-seco-cycloart-4(28),24-diene-3,26-dioic acid (2) (Yang et al 2010), mangiferonic acid (3) (Zhang et al 2003), friedelin (4) (Akihisa et al 1992), epifriedelanol (5) (Salazar et al 2000) and b-amyrine (6) (Mahato & Kundu 1994)), as well as two tocopherol trimers IVa (7) and IVb (8) (Row et al 2007) (Figure 1). Structures of known compounds were determined by comparison of their spectral data with those previously reported in the literature.…”
Section: Resultsmentioning
confidence: 99%